The effects of medium chain fatty acids as alternatives to zinc oxide or carbadox in nursery pig performance - Bone, Madison L.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
There is an increased consumer pressure to limit the use of feed based antibiotic in nursery pig diets. A total of 360 weanling pigs (DNA 200×400; 5.4 ± 0.07 kg) were used in a 35-d growth experiment with 6 treatments to evaluate MCFA as an alternative to ZnO or carbadox to examine the outcome of their ADG, BW, ADFI, and G:F. A completely randomized design was conducted using 10 replicates pens per treatment with 6 pigs per pen. The treatments were 1) control; 2) 3,000 ppm ZnO in Phase 1 and 1,500 ppm ZnO in Phase 2; 3) 50 g/ton carbadox; 4) 1% blend of C6:C8:C10; 5) 1% Feed Energy R2 (Feed Energy Corp, Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). The data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC) with pens being the Experiential Unit. The treatment diets had two phases, Phase 1 d 0 to 7, Phase 2 d 8 to 19, with a common diet fed from d 20 to 35. From d 0 to 19, pens fed ZnO or carbadox had greater (P<0.05) ADG than pens fed control or R2. The overall treatment shows there was no significant change in the G:F (P=0.320). The results of this experiment suggest that feeding ZnO and carbadox will have ahigher ADG (P=0.012) and ADFI (P=0.001) in weanling pigs. FORMI GML had a similar growth performance, however additional research is needed to confirm if certain MCFA could replace feed-based antibiotics in commercial swine production.
Keywords: Spring 2019